2016
DOI: 10.24903/sj.v1i1.15
|View full text |Cite
|
Sign up to set email alerts
|

The EFL Students' Narrative Paragraph Writing of The Second Semester Students of State Institute of Islamic Studies (IAIN) Samarinda: A Syntactic Analysis

Abstract: This study concerned on the EFL students' ability and analyzed the sentence patterns of syntax on the narrative paragraph writing. The QUANT-QUAL of mixed methods design was used in this study. The quantitative data gathered from the test of narrative paragraph writing by involving 30 EFL students of IAIN Samarinda. The qualitative data gathered from the 10 selected documents of narrative paragraph writing that met the criteria. The findings showed that the EFL students' ability of narrative paragraph was cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The current study revealed that the Indonesian EFL students' ability of Islamic State Institute (IAIN) Samarinda in writing comparison and contrast essay is Dinamika Ilmu, Volume 19(1), 2019 categorized in good scores and followed by their writing aspects ability namely content, organization, vocabulary, grammar, and mechanics. This findings were relevant found by Sanu (2016) and Husin & Nurbayani (2017) who studied the EFL students of IAIN Samarinda and revealed that the quality of academic paper writing was good (Husin & Nurbayani, 2017) and also their English narrative paragraph writing (Sanu, 2016). Moreover, the studies of Rasyidah & Antoni (2014), Cahyono et al (2016), and Irwan et al (2018), similarly reported that the Indonesian EFL students' academic essay writing ability was satisfied.…”
Section: E Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The current study revealed that the Indonesian EFL students' ability of Islamic State Institute (IAIN) Samarinda in writing comparison and contrast essay is Dinamika Ilmu, Volume 19(1), 2019 categorized in good scores and followed by their writing aspects ability namely content, organization, vocabulary, grammar, and mechanics. This findings were relevant found by Sanu (2016) and Husin & Nurbayani (2017) who studied the EFL students of IAIN Samarinda and revealed that the quality of academic paper writing was good (Husin & Nurbayani, 2017) and also their English narrative paragraph writing (Sanu, 2016). Moreover, the studies of Rasyidah & Antoni (2014), Cahyono et al (2016), and Irwan et al (2018), similarly reported that the Indonesian EFL students' academic essay writing ability was satisfied.…”
Section: E Discussionsupporting
confidence: 59%
“…Concerning the research findings above, there was also difference of research findings concerning the Indonesian EFL students' essay writing. Sanu (2016) and Husin & Nurbayani (2017) who investigated the Indonesian EFL students' writing ability at IAIN Samarinda, East Kalimantan and reported that their academic paper writing was good quality (Husin & Nurbayani, 2017) and also their English narrative paragraph writing (Sanu, 2016). Rasyidah & Antoni (2014) organized their study in Riau and similarly noted the Indonesian EFL learners had satisfied proficiency in critical essay writing.…”
Section: A Introductionmentioning
confidence: 99%
“…Other works such as Mohammed (2015), Sanu (2016), and Persada (2016) investigate parts of language i.e. grammatical problem, writing paragraph skill, and writing short article.…”
mentioning
confidence: 99%
“…Furthermore, many studies that have been investigated regarding errors in grammar have been carried out such as (Febriyanti & Sundari, 2016;Heryanti et al, 2017;Sanu, 2016;Sukarno, 2016). Generally, the studies are more viewed from the perspective of essays and narrative paragraph writing.…”
Section: Introductionmentioning
confidence: 99%